Penggunaan Metode Crossover Learning dalam Meningkatkan Semangat Belajar Tematik Peserta Didik - St. Nurhafsa Jalil; Ayyub Dg Pananrang; Delima Delima (Universitas Islam Darud Da'wah Wal-Irsyad A.G.H. Abdurrahman Ambo Dalle, 2025)
Thematic learning is an integrated learning approach that emphasizes student involvement in learning. Through thematic learning, students are expected to learn and play with high creativity. Thematic learning is student-centered because it requires students to actively learn the concepts of the material being taught. This research will focus on the use of the crossover learning method to enhance the enthusiasm for thematic learning in fourth-grade students at Saludengen Elementary School, Tommo District, Mamuju Regency. The main objectives are the crossover learning method, learning enthusiasm, and thematic learning. This type of research can be classified as descriptive qualitative field research, namely research that aims to systematically analyze and present facts about the actual state of the object. The author used several approaches deemed helpful in the research, including pedagogical, psychological, and communication approaches. Based on several interviews, it can be concluded that teachers who struggle to implement effective teaching methods, particularly the use of the crossover learning method in thematic learning in fourth-grade students at Saludengen Elementary School, Tommo District, Mamuju Regency, significantly affect students' absorption and focus in receiving the material.